Development of an Air Quality Monitor for Increased Productivity - Albinsson, Erik; Karlsson, Måns (My University, 2024)
In the modern world, air pollution in densely populated areas is increasingly becoming more of a problem. This is well known to affect personal health negatively, but lesser known is also the impact on productivity and human cognition. With products for measuring air quality is a developed market the products connecting it to productivity and providing recommendations to improve it are far less. This thesis is therefore set out to explore the effects on productivity from poor air quality and to develop a product as a solution. Air quality is found to affect productivity through many metrics; temperature, humidity, volatile organic compounds, carbon dioxide and particulate matter are some of the most impactful parameters and becomes the aim to monitor for this project. It is found that productivity in a poorly ventilated room, which is not that uncommon, can degrade by as much as 50% [1]. Creating awareness of this effect could possibly increase human productivity around the world by a significant margin and result in overall improvements. For the product to be successful it has to comply with the current market and user needs. This is therefore an important research topic sought to understand for the development of the product. A thorough and systematic product development methodology has been used to arrive at an optimal concept solution for the air quality monitor. As a goal and for introduction to the market, a minimum viable product has been developed with the purpose of giving users an initial understanding of the monitor. This prototype is used as proof of concept and to communicate the project proposal to external parties
Keywords: Air Quality; Air Quality Monitor; Productivity; Human cognition; Awareness; Product Development; Minimum Viable Product